Variability in HOMA-IR, Lipoprotein Profile and Selected Hormones in Young Active Men - Anna Keska; Grazyna Lutoslawska; Anna Czajkowska; Joanna Tkaczyk; Krzysztof Mazurek (The Scientific World Journal)
Resistance to insulin actions is contributing to many metabolic disturbances. Such factors as age, sex, nutrition, body fat, and physical activity determine body insulin resistance. Present study attempted to asses insulin resistance and its metabolic effects with respect to energy intake in young, lean, and active men. A total of 87 men aged 18–23 participated in the study. Plasma levels of glucose, insulin, lipoproteins, cortisol, and TSH were determined. Insulin resistance was expressed as Homeostasis Model Assessment for Insulin Resistance (HOMA-IR) and calculated using homeostatic model. The median value of HOMA-IR (1.344) was used to divide subjects into two groups. Men did not differ in anthropometric parameters, daily physical activity, and plasma TSH and cortisol levels. However, in men with higher HOMA-IR significantly lower daily energy intake was observed concomitantly with higher TG, TC, and HDL-C concentrations in plasma versus their counterparts with lower HOMA-IR. Exclusively in subjects with higher HOMA-IR significant and positive correlation was noted between HOMA-IR and TC and LDL-C. We concluded that despite a normal body weight and physical activity, a subset of young men displayed unfavorable changes in insulin sensitivity and lipid profile, probably due to insufficient energy intake.